2012
DOI: 10.1073/pnas.1113166109
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and Purkinje cell loss in autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS)

Abstract: Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is a childhood-onset neurological disease resulting from mutations in the SACS gene encoding sacsin, a 4,579-aa protein of unknown function. Originally identified as a founder disease in Québec, ARSACS is now recognized worldwide. Prominent features include pyramidal spasticity and cerebellar ataxia, but the underlying pathology and pathophysiological mechanisms are unknown. We have generated an animal model for ARSACS, sacsin knockout mice, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
193
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(205 citation statements)
references
References 53 publications
12
193
0
Order By: Relevance
“…Sacsin localizes to mitochondria where it interacts with Drp1 and might be involved in the assembly of higher-order complexes containing the fission enzyme. Consistent with this notion, fibroblasts from ARSACS patients exhibit severe hyperfusion of the mitochondrial network, which is recapitulated by knockdown of sacsin in neurons (Girard et al, 2012). Additionally, fibroblasts from ARSACS patients and fibroblasts in which sacsin had been knocked down both show a decrease in the formation of Drp1 foci at mitochondria, suggesting that sacsin stabilizes active fission complexes at mitochondria (Bradshaw et al, 2016).…”
Section: Mitochondrial Dynamics In Neurodegenerative Diseasessupporting
confidence: 63%
“…Sacsin localizes to mitochondria where it interacts with Drp1 and might be involved in the assembly of higher-order complexes containing the fission enzyme. Consistent with this notion, fibroblasts from ARSACS patients exhibit severe hyperfusion of the mitochondrial network, which is recapitulated by knockdown of sacsin in neurons (Girard et al, 2012). Additionally, fibroblasts from ARSACS patients and fibroblasts in which sacsin had been knocked down both show a decrease in the formation of Drp1 foci at mitochondria, suggesting that sacsin stabilizes active fission complexes at mitochondria (Bradshaw et al, 2016).…”
Section: Mitochondrial Dynamics In Neurodegenerative Diseasessupporting
confidence: 63%
“…2 In addition to developmental abnormalities in the TPF and their mechanical effects on the CST, axonal degeneration and, more extensively, demyelination in cerebral WM may explain a wide range of neurologic abnormalities other than spasticity and the progressive nature of the disease. Recently, Girard et al 30 showed localization of sacsin to mitochondria and a cascade of detrimental effects resulting in neuronal cell death by loss of sacsin function in knockout mice. These authors further suggested the presence of some common pathophysiologic features between ARSACS and some other neurodegenerative diseases with mitochondrial impairment such as Alzheimer, Parkinson, and Huntington disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not surprising that mitochondrial dysfunction and oxidative stress have been implicated in various NDs (Burte et al, 2015;Chaturvedi and Flint Beal, 2013;Karbowski and Neutzner, 2012), such as Alzheimer's disease (AD) (Friedland-Leuner et al, 2014;Simoncini et al, 2015), Parkinson's disease (PD) (Haelterman et al, 2014;Hang et al, 2015;Overk and Masliah, 2014;Ryan et al, 2015), Huntington's disease (HD) (Ayala-Pena, 2013;Guedes-Dias et al, 2015;Labbadia and Morimoto, 2013;Tsunemi and La Spada, 2012) and Amyotrophic lateral sclerosis (ALS) (Cozzolino et al, 2013;Duffy et al, 2011;Magrane and Manfredi, 2009). Importantly, in inherited recessive ataxias such as Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) or Friedreich's ataxia, mutations within mitochondriaassociated proteins are the most frequent cause underlying the development of these disease (Calabrese et al, 2005;Criscuolo et al, 2015;Girard et al, 2012). These observations are not unexpected considering that PCs are amongst the most active neurons in the central nervous system and have a high energy demand that makes them particularly susceptible to mitochondrial impairment or dysfunction (Zeviani et al, 2012).…”
mentioning
confidence: 99%